2011 IEEE International Conference on Bioinformatics and Biomedicine 2011
DOI: 10.1109/bibm.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Short Sequence Mapping Tools

Abstract: Background: The development of next-generation sequencing instruments has led to the generation of millions of short sequences in a single run. The process of aligning these reads to a reference genome is time consuming and demands the development of fast and accurate alignment tools. However, the current proposed tools make different compromises between the accuracy and the speed of mapping. Moreover, many important aspects are overlooked while comparing the performance of a newly developed tool to the state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…Tools have been specifically designed to manipulate SAM/BAM files (for example, to quickly sort, merge or retrieve alignments), including the widely used SAMtools (Li et al, 2009b) and Picard. Several benchmarking studies have empirically compared short read alignment methods with respect to various metrics (that is, runtime, sensitivity and accuracy) using both simulated and real data sets from different organisms (Holtgrewe et al, 2011;Ruffalo et al, 2011;Fonseca et al, 2012;Lindner and Friedel, 2012;Schbath et al, 2012;Hatem et al, 2013;Caboche et al, 2014;Shang et al, 2014;Highnam et al, 2015). These analyses demonstrated that results depend strongly on the properties of the input data, and thus there is no single method best suited for all scenarios.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Tools have been specifically designed to manipulate SAM/BAM files (for example, to quickly sort, merge or retrieve alignments), including the widely used SAMtools (Li et al, 2009b) and Picard. Several benchmarking studies have empirically compared short read alignment methods with respect to various metrics (that is, runtime, sensitivity and accuracy) using both simulated and real data sets from different organisms (Holtgrewe et al, 2011;Ruffalo et al, 2011;Fonseca et al, 2012;Lindner and Friedel, 2012;Schbath et al, 2012;Hatem et al, 2013;Caboche et al, 2014;Shang et al, 2014;Highnam et al, 2015). These analyses demonstrated that results depend strongly on the properties of the input data, and thus there is no single method best suited for all scenarios.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A thorough survey of sequence aligners is beyond the scope of our work and we refer the reader to [18], [19], [20], [21], [22], [23]. We primarily focus on parallel sequence mapping tools and relevant methods in this section.…”
Section: Related Workmentioning
confidence: 99%
“…Hatem et al show in a recent performance benchmark that current state-of-the-art sequence alignment tools can align 1 billion base pairs in one hour [7]. In contrast, current DNA sequencers have already a throughput of 2.5 billion base pairs per hour [12].…”
Section: Efficient Large-scale Data Processingmentioning
confidence: 99%